Can Interpersonal Behavior Influence the Persistence and Adherence to Physical Exercise Practice in Adults? A Systematic Review - Rodrigues, Filipe; Bento, Teresa; Cid, Luís; Pereira Neiva, Henrique; Teixeira, Diogo; Moutão, João; Almeida Marinho, Daniel; Monteiro, Diogo (Frontiers in Psychology, 2018)
Objective: Motivation seems to be a fundamental indicator of long-term physical exercise adherence. Self-Determination Theory argues that social environment plays a central role in the satisfaction of the basic psychological needs, which might directly affect the quality of one’s motivation. Individuals who appear to be more self-determined tend to persist longer at a certain behavior. Therefore, this body of work intends to analyze the relationship between motivational variables and behavioral outcomes in the exercise context, having as a theoretical background the Self-Determination Theory. Methods: This systematic review was conducted through an electronic search on Web of Science, PubMed, SPORTDiscus, and PsycINFO. Data such as instruments, main predictors and results were collected from studies published between 1985 and 2018. A total of 35 empirical studies were considered for a detailed analysis. Results: Results enhance the relevance of the autonomy support performed by exercise professionals, as well as the major contribution that these behaviors have towards the satisfaction of the basic psychological needs, besides the inherent benefits of developing more autonomous regulations. According to the literature, few studies have analyzed interpersonal thwarting behavior and the way this relates to basic psychological needs’ frustration. However, there seems to be a negative relationship between less self-determined motivational regulations and exercise practice. Conclusion: According to this review, interventions based on Self-Determination Theory appear to be fundamental when it comes to promoting the maintenance of a long-term exercise practice. However, despite the existence of numerous cross-sectional studies that demonstrate a positive correlation between Self-Determination Theory and behavioral outcomes in the exercise context, longitudinal research that analyzes all six dimensions of interpersonal behaviors and their relationship with persistence and adherence to exercise proves to be crucial.